Women offenders' experiences of rehabilitation in a South African correctional centre. Issue 1 (2nd January 2022) - Qhogwana, Sibulelo; Segalo, Puleng
Abstract : This study explored gendered rehabilitation of women in correctional spaces and the systems and structures that recreate inequities in women's incarceration experiences. Eighteen black women completed in-depth interviews on their offender rehabilitation experiences. Their age ranged from 23 to 69 years old, and they were mostly incarcerated for violent offenses. Thematic analysis of the interview data yielded the following themes: lack of active participation in rehabilitation processes; exclusion through language and religion; and enforcement of domestication for incarcerated women. Social justice centred approaches that recognise the diversity (classification, socio-cultural background, and gender dynamics) of people inhabiting correctional centres would help reduce disparities in correctional rehabilitation that disadvantage women offenders.